Functional investigation of bone implant viability using radiotracers in a new model of osteonecrosis (Clinics, 2016)
OBJECTIVES: Conventional imaging methods are excellent for the morphological characterization of the consequences of osteonecrosis; however, only specialized techniques have been considered useful for obtaining functional information. To explore the affinity of radiotracers for severely devascularized bone, a new mouse model of isolated femur implanted in a subcutaneous abdominal pocket was devised. To maintain animal mobility and longevity, the femur was harvested from syngeneic donors. Two technetium-99m-labeled tracers targeting angiogenesis and bone matrix were selected. METHODS: Medronic acid and a homodimer peptide conjugated with RGDfK were radiolabeled with technetium-99m, and biodistribution was evaluated in Swiss mice. The grafted and control femurs were evaluated after 15, 30 and 60 days, including computed tomography (CT) and histological analysis. RESULTS: Radiolabeling achieved high (>;95%) radiochemical purity. The biodistribution confirmed good blood clearance 1 hour after administration. For 99mTc-hydrazinonicotinic acid (HYNIC)-E-[c(RGDfK)2, remarkable renal excretion was observed compared to 99mTc-methylene diphosphonate (MDP), but the latter, as expected, revealed higher bone uptake. The results obtained in the control femur were equal at all time points. In the implanted femur, 99mTc-HYNIC-E-[c(RGDfK)2 uptake was highest after 15 days, consistent with early angiogenesis. Regarding 99mTc-MDP in the implant, similar uptake was documented at all time points, consistent with sustained bone viability; however, the uptake was lower than that detected in the control femur, as confirmed by histology. CONCLUSIONS: 1) Graft viability was successfully diagnosed using radiotracers in severely ischemic bone at all time points. 2) Analogously, indirect information about angiogenesis could be gathered using 999mTc-HYNIC-E-[c(RGDfK)2. 3) These techniques appear promising and warrant further studies to determine their potential clinical applications.